Proposed Balochistan agriculture 2021 - Rana, Abdul Wajid; Moeen, Muhammad Saad; Shikoh, Sania Haider; Davies, Stephen (International Food Policy Research Institute, 2021)
Balochistan is the largest province of Pakistan comprising 44% of the country’s total land mass with a population of 12.34 million (5.9 percent of total population of the country), its southern border of Balochistan makes up two-thirds (770 KM) of the national coastline, giving assess to a large pool of aqua-resources. The province has low population density and provides vast rangeland for goats, sheep, buffaloes, cattle, camels, and other livestock. It is bestowed with natural and locational resources and is the second major supplier of natural gas which supports the country’s industrialization and economic centers. The province also potentially has large deposits of coal, copper, lead, gold, and other minerals. As a frontier province, it is ideally situated for trade with Iran, Afghanistan, Central Asia, and the Persian Gulf countries, and now with western China through Gwadar Port and China-Pakistan Economic Corridor.